EVALUATION OF MONOLITHIC COLUMN FOR INORGANIC MERCURY AND METHYLMERCURY DETERMINATION IN FISH SAMPLE ANALYSIS - Manuel A. Bravo; Ornella Riquelme; Sonnia Parra; Jan Bergmann; Waldo Quiroz (Journal of the Chilean Chemical Society, 2019)
In the present work, the applicability of a monolithic column was evaluated for mercury speciation analysis in certified and real fish samples. The influence of the flow and composition of the mobile phase (2-mercaptoethanol concentration and methanol content) on the retention times of iHg and MeHg was evaluated. The optimal separation conditions were achieved for a mobile phase containing 5 % methanol and 0.02 % mercaptoethanol in acetate buffer (pH 5.0) at a flow rate of 1.6 ml min-1. Different extraction conditions were studied to analyze a certified reference material with the optimized methodology and the best results (93 % recovery) were obtained for microwave-assisted extraction with a mixture of HCl 6 M + NaCl 0.5 M. Finally, the proposed method was satisfactorily applied to real fish samples collected from different markets in the central region of Chile, presenting levels ranging from 0.73 – 3.4 mg kg-1.